Repo markets, counterparty risk and the 2007/2008 liquidity crisis - Christian Ewerhart; Jens Tapking (European Central Bank (ECB), 2008)
A standard repurchase agreement between two counterparties is considered to examine the endogenous choice of collateral assets, the feasibility of secured lending, and welfare implications of the central bank's collateral framework. As an important innovation, we allow for two-sided counterparty risk. Our findings relate to empirical characteristics of repo transactions and have an immediate bearing on market developments since August 2007.
Keywords: G21; G32; E51; 330; collateral; Counterparty risk; haircuts; liquidity; repurchase agreements; Geldmarkt; Handelsvolumen der Börse; Risikomanagement; Repo-Geschäft; Bankenliquidität; Theorie; Welt